Pengaruh Iklan Layanan Masyarakat di Media Sosial tentang GOLPUT Terhadap Pendapat Generasi Milenial di Fakultas Ilmu Sosoial dan Ilmu Politik, Universitas Islam Makassar (Studi Eksperimental) - nfn Haerul (Journal of Communication Sciences (JCoS), 2019)
This research was conducted to determine the effect of public service advertisements on social media about abstentions on the opinion of millennial generation in the sospol faculty, Makassar Islamic University. This research uses a quantitative method using an experimental design and is processed with the help of SPSS. Respondents in this study were drawn from students in 2016, 2017 and 2018 from 4 majors totaling 609 people. Samples selected in this study were 73 respondents with 10% precision. The results showed that there were significant changes in the sample after watching public service advertisement videos in assessing voter participation in the 2019 election. Hypothesis testing proved that the value of sig. 2-tailed is smaller than α 0.05 (0,000 <0.05). The difference between -435 to -.166 (90% confidence interval of the difference).